Penggunaan Video dalam Pengajaran Berbicara: Sebuah Penelitian Tindakan Kelas (PTK) - Hasrat Sozanolo Harefa (INTELEKTIUM, 2021)
This study aims to describe the factors that support students' ability in the learning process to speak using video. This research was classroom action research. Classroom action research was done in four steps: planning, action, observation, and reflection. Quantitative data was gained from the score of the student's speaking test. The test was given at the end of every cycle. The qualitative data was collected through the result of observation. It described the factors that support the students' ability to speak based on the result observation from the collaborator activities both the students and the researcher itself. The research aimed to explain how video can increase students' speaking skills in the second semester of the English Education Study Program for IKIP Gunungsitoli. Using video can increase students' skills in speaking. Quantitative data support it included test results in every cycle. The quantitative data show that students have improved speaking skills in every cycle using video and reaching the indicator of success. The students' ability to speak cannot pass the score standard in the cycle because most students cannot convey their ideas about the material. However, in cycle II, there is increasing in student's ability to speak. The quantitative data also is supported by the qualitative data through observation results. The observation sheet result describes that the students' activities improved every meeting by using video.